Safety climate in the operating room: Translation, validation and application of the Safety Attitudes Questionnaire - Pinheiro,João Pedro Alexandre (2016)
Background Safety climate assessment is increasingly recognized as an important factor in healthcare quality improvement, especially in operating rooms (OR). One of the most commonly used and rigorously validated tools to measure safety culture is the Safety Attitudes Questionnaire (SAQ). This study presents the validation of the Operating Room Version of the SAQ (SAQ-OR) for use in Portuguese Hospitals. The psychometric properties of the translated questionnaire are also presented. Methods The original English version of the SAQ-OR was translated and adapted to the Portuguese setting by forward-backward translation method and applied in a central public hospital. Scale psychometrics were analyzed using Cronbach's alpha and inter-correlations among the scales. Results The internal consistency test yielded values around 0.9 for all 73 items. The CFA and its goodness-of-fit indices (SRMR 0.05, RMSEA 0.002, CFI 0.90) showed an acceptable model fit. Inter-correlations between the factors safety climate, teamwork climate, job satisfaction, perceptions of management, and working conditions showed moderate correlation with each other. 82 valid questionnaires were analyzed revealing significant differences in communication ratings between different jobs, mainly between surgeons (4.2) and between nurses and surgeons (2.9). Working conditions and job satisfaction have the highest score with 3.8 and 3.5, respectively, and perceptions of management have the lowest score (2.8). Conclusion The Portuguese translation of the SAQ-OR reveals good psychometric properties for studying the organizational safety climate, however larger and further studies are required to compensate the lack of subjects in some items. Like other studies, this scale seems to be an acceptable to adequate tool to evaluate the safety climate. Results allowed to conclude that working conditions and job satisfaction are satisfactory. However, there is latitude for improvement, especially in the involvement of the management bodies as this factor has the lowest score for the majority of healthcare professionals.